'Click'-BINOLs: A New Class of Tunable Ligands for Asymmetric Catalysis - Beckendorf, Stephan; Mancheño, Olga García (Synthesis, 2012)
A new class of easily tunable 1,2,3-triazole-BINOL ligands, 'click'-BINOLs, have been synthesized from readily available alkynes and several azido-BINOL derivatives using the powerful Huisgen [3+2] cycloaddition 'click' approach. The activity of these ligands in asymmetric Lewis acid catalysis has been explored for the first time in the diethylzinc addition to aldehydes. The C2-symmetric ligand 1d showed an interesting catalytic behavior, which suggests the non-innocent participation of the triazole units. Thus, good enantioselectivities (up to 86% ee) were obtained by both the right selection of the substitution pattern at the triazole ring and the fine tuning of the reaction conditions.
Keywords: Lewis acids; asymmetric catalysis; 'click' chemistry; BINOL ligands; alkynes; aldehydes; diethylzinc additions